Education Science, Humanities Search Synergistic Technologies of Education - Irina Viktorovna Burkina (Наука. Инновации. Технологии)
This paper presents a brief analysis of the synergy humanitarian search technology education from the standpoint of the requirements of the problems of formation and development of modern Education science. Introduced innovative pedagogical interpretation opens integrative and innovative look at the implementation of humanitarian technologies in the construction of an integrated system of modern education.